PERMAINAN TRADISIONAL SENGALAUAN UNTUK PENGEMBANGAN MOTORIK KASAR ANAK USIA 5-6 TAHUN DI DESA SEMATA KECAMATAN TANGARAN KABUPATEN SAMBAS - Nurhaliza Nurhaliza; Fadillah Fadillah; Lukmanulhakim Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractChildren in Semata Village, Tangaran District, Sambas Regency in playing activities, some are still less able to run, there are children who fall while playing, are less able to change directions, are less able to run zigzags and are less able to make evasive movements while playing, because play activities carried out by children tend not to move actively for their gross motor skills. This study aims to develop gross motor skills in children aged 5-6 years in Semata village, Tangaran district, Sambas regency. The research method used is qualitative with a phenomenologic al approach. Data collection tools used in this research were observation sheets, interview guidelines and documentation with data sources of 9 children. The results showed that 1)The Sengalauan begins with osom or hompimpa or cang kacang panjang, ending with the player's agreement, namely disconnecting the right and left index fingers that are connected or saying I'm done, which is played on field and water where the players limit the playing area; 2) the child is able to use his muscles to run, jump with big strides and not fall; 3) run fast and can dodge quickly; 4) can change directions on the fly, zigzag, and perform evasive moves.Keywords: Gross Motor Development of Children Aged 5-6 year, Sengalauan Game